The Impact of Redistribution of Income on Nigeria Economic Growth and Stability (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examines the impact of income redistribution on Nigeria’s economic growth and stability. Annual data covering the period 1990 to 2025 were sourced from the World Bank, National Bureau of Statistics, World Development Indicators and the Central Bank of Nigeria. The variables analysed include Real GDP, Personal Income Tax (PIT), the Gini coefficient, Inflation Rate, Health, and Hosing. Methodologically, the study employs Autoregressive Distributed Lag (ARDL) framework to analyze both short-run and long-run dynamics. The Bounds Test confirms the existence of a long-run cointegrating equilibrium, while the Error Correction Model (ECM) estimates approximately 88.8% speed of adjustment within a year. The empirical findings reveal a positive long-run relationship between economic growth and PIT, health expenditure, and housing. Specifically, PIT demonstrates a significant positive impact on economic growth in the long run but exhibits a negative effect in the short run. Conversely, inflation acts as the primary inhibitor of macroeconomic stability, depicts a persistent negative impact on economic growth. High inflation further worsens income disparity by widening the gap between the rich and the poor. This structural pressure emphasises the key role of Personal Income Tax as a stabilizing mechanism to foster economic growth in Nigeria. Based on these findings, the study offers three primary recommendations. First, policymakers must strengthen PIT administration by widening the tax base, mitigating evasion, and enforcing compliance within the informal sector. Second, public expenditure on health and housing must be expanded and efficiently managed. Targeted investments in healthcare infrastructure and affordable housing are vital to build human capital, enhance labour productivity, and stimulate long-term growth. Finally, inequality-reduction policies must prioritize vulnerable, low-income households to ensure inclusive growth and social cohesion.